Microbiological quality and pH changes of honey produced by stingless bees, Heterotrigona itama and Geniotrigona thoracica stored at ambient temperature - Mohd Nizam Lani,; Amirah Hazirah Zainudin,; Shamsul Bahri Abdul Razak,; Azlina Mansor,; Zaiton Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Meliponini honey is one type of stingless bee honey. Although honey has been widely used as a natural remedy, understanding on how storage affect the microbiological quality and pH in stingless honey is still scarce. This study was carried out to determine the microbial quality of honey produced by stingless bees, Heterotrigona itama and Geniotrigona thoracica during ambient storage for 6 weeks. The changes in microbiological analysis was determined for Aerobic Plate Count (APC), yeast count and Bacillus count. Lactic acid bacteria (LAB) were isolated using three types of media, namely, MRS agar, MRS agar with 0.8% CaCO3 and MRS agar with 1% glucose. Detection of Clostridium was done using anaerobic egg-yolk agar and cook meat medium. Results showed that Aerobic Plate Count ranged between 102 to 105 CFU/g for both samples. However, yeast count showed the range between 102 to 106 CFU/g, which higher than APC. Both honey samples showed low in Bacillus count. The LAB counts on three media were significantly higher for the first month of storage, then decreased gradually after fifth week. Storage of honey had reduced the pH in both honey samples to pH 2. Clostridium was not detected in all samples.